(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
In this paper we have discussed about e-Governance and its implementation in various fields like agriculture, banking, RTI, education and health. The text then covers the section related to use of social networking sites and the indispensable part it has become of our lives. The main objective of this paper is to analyze the role of electronic media and how it has influenced our day to day lives. A comparative table is also presented that reflects how electronic media has changed the way we manage our daily affairs.